Low temperature, mechanical wound, and exogenous salicylic acid (SA) can stimulate the SA signaling molecule as well as its downstream pathway and the formation of fruiting bodies in Flammulina filiformis - Li, Ziyan; Wen, Jin; Jing, Zhuohan; Li, Hui; Huang, Jiahua; Yuan, Chengjin; Xian, Lijun; Gao, Lingling; Zhu, Jian; Xie, Baogui; Tao, Yongxin (Frontiers in Microbiology, 2023)
Low temperature (LT) and mechanical wound (MW) as two common physics methods, have been empirically used in production to stimulate the primordia formation of Flammulina filiformis, which is typically produced using the industrial production mode. However, the detailed effect on the fruiting bodies formation and important endogenous hormones and signaling pathways in this process is poorly understood. In this study, LT, MW, their combination MW+LT, and low concentration of SA (0.1 mM SA) treatments were applied to the physiologically mature mycelia of F. filiformis. The results showed that the primordia under the four treatments began to appear on the 5th -6th days, Compared with 12th days in the control (no treatment). MW+LT treatment grew out the largest number of primordia (1859 per bottle), followed by MW (757), SA (141) and LT ( 22), compared with 47 per bottle in the control. HPLC results showed that the average contents of endogenous SA were significantly increased by 1.3 to 2.6 times under four treatments. Total 11 SA signaling genes were identified in the F. filiformis genome, including four NPR genes (FfNpr1-4), five TGA genes (FfTga1-5) and two PR genes (FfPr1-2). FfNpr3 with complete conserved domains (ANK and BTB/POZ) showed significantly up-regulated expression under all four above treatments, while FfNpr1/2/4 with one domain up-regulated under partial of four treatments. FfTga1-5 and FfPr1-2 showed 1.6-fold to 8.5-fold significant up-regulation with varying degrees in response to four treatments. The results suggested that there was a correlation among "low temperature/mechanical wound -SA signal -fruiting bodies formation", it will help to understand the roles of SA hormone as well as SA signaling pathway genes in the formation of fruiting bodies in fungi.